2016
DOI: 10.1016/j.bjane.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Use of tranexamic acid in primary total knee replacement: effects on perioperative blood loss

Abstract: Tranexamic acid reduced postoperative bleeding without promoting thromboembolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Longer surgical time also contributed to the results of more perioperative blood loss in the group tourniquet releasing before wound closure. Perioperative blood loss in TKA patients has been reported in association with drain clamping technique, [37] application of compression dressing, [38] intravenous antifibrinolytic therapy, [39] tourniquet application time, [33] and early rehabilitation programs. [10] Besides that, an early use of continuous passive motion machines could increase blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Longer surgical time also contributed to the results of more perioperative blood loss in the group tourniquet releasing before wound closure. Perioperative blood loss in TKA patients has been reported in association with drain clamping technique, [37] application of compression dressing, [38] intravenous antifibrinolytic therapy, [39] tourniquet application time, [33] and early rehabilitation programs. [10] Besides that, an early use of continuous passive motion machines could increase blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found in the literature also support its use for the same purpose. 14,15,17,21,[23][24][25][26][27][28] As for the instrumentation used, overall PSI showed lower blood loss in the group not using TXA. Kizaki et al reported similar findings in a 2019 meta-analysis, also giving the advantage to PSI over CI in terms of blood loss but without statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Blood transfusions have an undeniable value but they also pose some risks such as infections, immunological reactions, and even death. 6,14,15,[19][20][21][22] The trauma caused by surgery releases from the vascular endothelium tissue plasminogen activator (TPA), the enzyme responsible for converting plasminogen into plasmin, thereby activating fibrinolysis. 21 Tranexamic acid (TXA) is an antifibrinolytic synthetic drug that limits blood loss by inhibiting this conversion (►Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in conformity with what has been found by the previous researchers [2,11] . It has been sufficiently shown that tranexamic acid administration is a useful tool to decrease postoperative blood loss in major orthopedic surgeries [12,13] . However, in spite of several studies performed, the most appropriate route of tranexamic acid administration remains controversial.…”
Section: Discussionmentioning
confidence: 99%